Critical Thinking Skills and Information-Seeking Anxiety Relationship among Senior High School Students - Dedy Dwi Putra; Maya Umi Hajar (Universitas Sebelas Maret, 2025)
This study explores the relationship between critical thinking skills and information-seeking anxiety among senior high school students in the digital era. The research was motivated by students' difficulties in evaluating the validity and relevance of information, which often leads to anxiety during the search process. Using a mixed-methods case study approach, the study involved 36 tenth-grade students from a high school in Malang City, Indonesia. The intervention was implemented through three science learning cycles using a Problem-Based Learning (PBL) model. Data on students' critical thinking skills were obtained from classroom dialogue transcripts and analyzed using the Transcript-Based Lesson Analysis (TBLA) based on Paul and Elder’s critical thinking framework. Information-seeking anxiety data were collected using the Information Seeking Anxiety Scale (ISAS) and supplemented with interview data. The findings revealed a progressive improvement in students' critical thinking skills across the three learning cycles, particularly in their ability to gather relevant information. Simultaneously, a strong negative correlation was found between critical thinking ability and information-seeking anxiety. Students with higher critical thinking skills experienced lower levels of anxiety, while students with lower critical thinking skills were more prone to anxiety, especially when encountering digital distractions and challenges in identifying credible information. The study highlights the importance of integrating active learning models, enhancing digital literacy, and providing structured training in information searching. These findings have implications for curriculum design and suggest future research should investigate additional factors, such as digital self-efficacy and learning motivation, that may influence the observed relationship.